2018
DOI: 10.1111/jvim.15315
|View full text |Cite
|
Sign up to set email alerts
|

Ethical conflict and moral distress in veterinary practice: A survey of North American veterinarians

Abstract: BackgroundConcerns about ethical conflicts, moral distress, and burnout in veterinary practice are steadily increasing. Root causes of these problems have not been rigorously identified. Little research has been done to evaluate the existence of moral distress in North American veterinarians or to explore its impact on career sustainability and poor well‐being.Hypothesis/ObjectivesEthical conflict and resultant moral distress are common occurrences in contemporary veterinary practice and negatively impact dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
142
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(183 citation statements)
references
References 20 publications
(18 reference statements)
1
142
1
5
Order By: Relevance
“…Official veterinarians may not have adequate professional qualifications to get through challenging client interactions when the clients also have serious personal problems (25). Versatility of work 12 (18) People (both work community and clients) met at work 10 (15) The responding official Finnish veterinarians required more training in interaction skills. This was quite opposite to the Irish governmental veterinarians who did not want to have more education in this area (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Official veterinarians may not have adequate professional qualifications to get through challenging client interactions when the clients also have serious personal problems (25). Versatility of work 12 (18) People (both work community and clients) met at work 10 (15) The responding official Finnish veterinarians required more training in interaction skills. This was quite opposite to the Irish governmental veterinarians who did not want to have more education in this area (25).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on the well-being of veterinarians and it has been shown that the rates of suicidal behavior [see for review (11)], stress (12)(13)(14), and mental health problems (12,15) are elevated. Causes of veterinarian stress include long work hours, conflicting client relations (16), interference with the work-home balance (17), low income, high debt (14), ethical conflicts, and moral distress (18).…”
Section: Introductionmentioning
confidence: 99%
“…Other difficult clinical decisions such as convenience euthanasia of a healthy animal and financial limitations of the client can cause great moral distress . Veterinarians reported that their training did not adequately prepare them to manage ethically challenging situations . As ethically challenging situations may lead to moral stress or moral distress, preparing veterinarians to navigate ethically challenging situations might be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the third interpretation of interdependence-interbeing-might end up paralyzing veterinary students. Moreover, moral problems in veterinary practice already represent a great challenge, not to mention the perils of moral distress that arise when professionals are insufficiently able to live up to their own moral ideals because of the way in which their working environment and its demands structure and restrict individual agency [40].…”
Section: Pedagogy Of Veterinary Ethics Educationmentioning
confidence: 99%
“…However, letting complexity and conflicting demands narrow and blunt moral agency should be prevented if only to protect the wellbeing of veterinarians themselves. Paradoxically, numbing oneself in order to deal with moral distress can easily backfire [40], which is why becoming aware of the ways in which one's agency is shaped over time, embedded within a certain environment, and confronted with a myriad of diverging expectations, could help to bolster robust moral agency.…”
Section: Pedagogy Of Veterinary Ethics Educationmentioning
confidence: 99%